The emblems of the Album of the Ljubljana Noble Society of St Dismas - Germ, Tine (Ars et humanitas, 2017)
The article discusses the sources for the iconography of emblems in the Album of the Ljubljana Noble Society of St Dismas (Archive of the Republic of Slovenia, ref. AS 1073, I/1) that has not yet been systematically addressed. The Album is a kind of memorial book of the Ljubljana Noble Society of St Dismas or Academia Unitorum, displaying the coats of arms, emblems and important data of their members. The book with exquisite full page illuminations is the most important illuminated manuscript of the Baroque era that survives in Slovenia. Recent research shows, that the idea of the academic memorial book and its concept are modelled on the Memorie, imprese, e ritratti de' signori Accademici Gelati de Bologna published in Bologna in 1672. Due to the specific context of the Album as a memorial book of St Dismas Society and a clearly articulated ambition of the patrons to create original individualized emblems, it is not easy to identify the possible sources let alone detect the direct influence. There are several emblem books to be taken into consideration and Alciati's Emblematum liber appears to be a valuable source of inspiration. However, the research in Renaissance and Baroque books of emblems shows that it is actually Mundus Symbolicus by Filippo Picinelli (first published as Mondo simbolico, Milan 1653) which seems to be of vital importance for the creators of the Album. Since the proud members desired original and personalized emblems, it was only natural to rely upon a popular encyclopaedic work with a huge collection of systematically arranged descriptions of emblems. Picinelli's book is actually a treasure-trove of ideas instigating new designs both in the sense of symbolic message and visual solutions, while the almost complete absence of illustrations prevents a simple reproduction of emblems. Due to their commitment to originality and the respect of the principles of St Dismas Society the members obviously found the traditional emblem books (where they could see prototypes including the picture) somehow less appealing. However, even when they use a traditional emblem book such as Alciati's Emblematum liber as a model, the authors (both patrons and painters) of the Album exhibit great inventiveness and creativity and never simply reproduce a prototype. The Album thus represent a unique series of original emblems that also indicate the commitment to established tradition and occasionally reveal a direct influence of a popular emblem book as demonstrated in the article.
Keywords: Alciati, Andrea; barok; Dolničar, Janez Gregor; emblematika; ikonografija; Picinelli, Filippo; renesansa; Spominska knjiga ljubljanske plemiške družbe sv. Dizma; Trost, Andrej